Mobilizing the transformative power of research for achieving the Sustainable Development Goals - Romero Goyeneche, Oscar Yandy; Ramirez, Matias; Schot, Johan; Arroyave, Felber (Research policy, 2022)
This paper addresses the important question of how research can support the implementation of the United Nations 17 sustainable development goals (SDGs) set out in the 2030 agenda. Much attention on this topic has so far coalesced around understanding and measuring possible synergies and trade-offs that emerge in the SDGs. We contribute to this discussion by arguing that it is necessary to move towards a focus on how SDGs are enabling transformative change. A conceptual approach is presented based on the notion that research should build bridges across three types of SDGs: ones that reflect socio-technical system change, directionality, and framework conditions. This proposition is explored empirically through a case study of Mexican scientific knowledge production using methods from bibliometric and social network analysis. Our results can help to provide a diagnostic of how knowledge production is contributing to the SDGs and can be used in science, technology and innovation policy, in particular transformative innovation policy. •Research on SDGs that links sociotechnical systems, directionalities and governance may help to advance a transformative agenda•Bibliometric coupling, triad networks and community cluster analysis shows how some SDGs work with each other in nexus-type relationships•Mapping emerging research clusters of SDGs can suggest how to unlock the transformative potential of scientific knowledge production•Pivoting research outputs around some directionality-related SDGs could help generate disruptive transformations